Research on Optimization of Power Emergency Material Dispatching for Beijing Winter Olympics - Yue Zhao (Hindawi Limited, 2021)
The Beijing Winter Olympic Games is an extremely important event, and the supply of electricity is the basis for it. In order to prevent the sudden loss of power to the event, it is necessary to carry out power repair and restore normal power supply in the shortest possible time. Contemporary research is less focused on the emergency repair of power systems. This thesis studies the dispatching of power emergency materials in two stages and in the first stage, the minimum gap rate and the shortest time for material dispatching and transportation are mainly considered, and the required types of power emergency materials are dispatched from the storage near the Olympic venues to various power failure points. In the second stage, aiming at the shortage of power emergency materials at each fault point, the power emergency materials will be dispatched from the rear national power grid regional material reserve to the power emergency materials reserve near the Olympic venues and then dispatched to each power fault point through the power emergency materials reserve. Finally, this paper verifies the effectiveness of the combination of the primary and secondary dispatching models in an example, providing a reference for further improving the emergency response capability of the Olympic venues and improving the safety system of the power system.